The role of intraflagellar transport in cilia maintenance - Werner, Sascha (2017)
"Cilia are microtubule-base protrusions from the surface of most cells in the human body. They can be found in species from all branches of the eukaryotic tree of life and were probably already present in the last eukaryotic common ancestor (Carvalho-Santos et al., 2011). In all ciliated species, cilia are crucial for the development and physiology of the organism, and they carry out many different functions ranging from motility to sensing (Choksi et al., 2014).(...)"